Thunderstorms, lightning, sprites and magnetospheric whistler-mode radio waves - Siingh, Devendraa; Singh, A.K.; Patel, R.P.; Singh, Rajesh; Singh, R.P.; Veenadhari, B.; Mukherjee, M. (My University, 2008)
Thunderstorms and the lightning that they produce are inherently interesting phenomena that have intrigued scientists and mankind in general for many years. The study of thunderstorms has rapidly advanced during the past century and many efforts have been made towards understanding lightning, thunderstorms and their consequences. Recent observations of optical phenomena above an active lightning discharge along with the availability of modern technology both for data collection and data analysis have renewed interest in the field of thunderstorms and their consequences in the biosphere. In this paper, we review the electrification processes of a thunderstorm, lightning processes and their association with global electric circuit and climate. The upward lightning discharge can cause sprites, elves, jets, etc. which are together called transient luminous events. Their morphological features and effects in the mesosphere are reviewed. The wide spectrum of electromagnetic waves generated during lightning discharges couple the lower atmosphere with the ionosphere/magnetosphere. Hence various features of these waves from ULF to VHF are reviewed with reference to recent results and their consequences are also briefly discussed.
Keywords: Thunderstorm; Global electric circuit; Climate; Sferics; Transient luminous events; Schumann resonances; Whistler-mode waves; ELF/VLF emissions; Lightning; Radio waves